Redes familiares en la inmigración hacia el Ensanche Este de Madrid (1860-1878) - Borja Carballo Barral (Centre de Recherches sur les Mondes Américains, 2008)
This paper will discuss the different patterns of family insertion developed by immigrants arrived to Madrid between 1860 and 1878. In spite of its lack of an industrial development, Madrid experimented during these decades an important demographic growth due to the constant arrival of new inhabitants in search for a job. Rather than analyse the raisons that impelled these immigrants to come to Madrid or enumerate which were their regions of origin, the aim of this paper is to describe and reconstruct the ways these immigrants managed to create their home at the great city. The different patterns of arrival to the city (alone, in couple or with a family yet formed) and the family networks they had at their disposal conditioned the status and the living conditions that the immigrants finally had in the city. The study presented is circumscribed to one of Madrid’s new neighbourhoods stemmed from capital’s urban enlargement: the Ensanche Este, whose municipal census has been analysed as main source of research.